Вечный идол: Новеллы о женских судьбах / Л. Третьякова - Третьякова Людмила (Изограф: ЭКСМО-Пресс, 2000)
Экземпляры: ЦБ (2001) / Инвентарный номер: 34050 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Т 66 / ББК: 84(2Рос=Рус)6